Optimum Generation Scheduling for Thermal Power Plants using Artificial Neural Network - Nagaraj Mudukpla Shadaksharappa (International Journal of Electrical and Computer Engineering (IJECE), 2011)
A simple method to optimize generation scheduling for thermal power plant using artificial neural network is presented. The optimal generation of generators is achieved considering operational and load constraints. The B- Coefficients are used to evaluate transmission loss in the system. The fuel cost of each unit in a plant is computed. The effectiveness of methodology is tested with six thermal power plants. A result of proposed method is compared with classical method. The artificial neural network method is quick. Hence, artificial neural network technique can be used in central load dispatch center.Keywords- Neural network, B-Coefficients, Fuel cost, Power loss, Real powerDOI:http://dx.doi.org/10.11591/ijece.v1i2.83